The THE INFLUENCE OF GREEN BANKING DISCLOSURE INDEX, PROFITABILITY, AND OPERATIONAL COST EFFICIENCY ON COMPANY VALUE IN INDONESIAN ISLAMIC COMMERCIAL BANKS FOR THE 2022-2024 PERIOD - Abduh, Muhammad Abduh; Suarsih; Kholida, Alda (PT Larva Wijaya Penerbit, 2025)
This study aims to analyze the influence of green banking disclosure, operational efficiency, and profitability on firm value in Islamic commercial banks in Indonesia during the period 2022–2024. This study was conducted to determine the extent to which sustainable banking practices, as reflected in the level of green banking disclosure, contribute to increasing firm value through increased efficiency and profitability. Secondary data were obtained from the annual reports of three Islamic commercial banks: Bank Syariah Indonesia, Bank Tabungan Pensiunan Nasional Syariah, and Bank Panin Dubai Syariah. The analysis was conducted using panel data regression with the assistance of Stata 17 software. The results show that green banking disclosure has a positive effect on firm value, meaning that the better the sustainability and environmental disclosure, the higher the market valuation of the company. Operational efficiency, measured by the operating expense ratio, has a negative effect on firm value, while profitability, measured by return on equity, has a positive and significant effect. These findings emphasize the importance of integrating sustainability performance and financial efficiency in increasing the long-term value of Islamic banks.